Dropshipping System from A Hybrid Contract Perspective - Deviyana Khoirotul Iswiyah; Fairuz Sabiq (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This research aims to determine the Dropshippimg Trading System on the Shopee Marketplace from a Hybrid Contract Perspective. The research is being offered in 2022-2023. The type of research in this research is field research and to achieve this goal the author uses a qualitative descriptive approach. Data collection was obtained through observation, interviews and documentation studies. Interviews were conducted with Dropshippers and Customers at Shopee Pasar. Data were analyzed using Milles and Huberman analysis, namely by data reduction, data presentation, and drawing conclusions or verification. The research results show that the practice of buying and selling using the Dropshippimg system on the Shopee Marketplace can be offered through several channels and the first thing to do is create an account. In terms of responsibilities and other processes, the practice meets the requirements and is harmonious in buying and selling, so the Dropshippimg system is allowed. There are several contracts in the Dropshippimg system on the Marketplace, namely Muḍarabah, Samsarah, Salam, and Wakalah bi Al-Ujrah. Muḍarabah occurs between the Supplier / Dropshipper and Shopee. Samsarah occurs between Dropshipper and Supplier. Salam occur between Customer and Dropshipper. Wakalah bi Al-Ujrah occurs between the Dropshipper and the shipping service.